2006
DOI: 10.1063/1.2385405
|View full text |Cite
|
Sign up to set email alerts
|

On-chip detection of ferromagnetic resonance of a single submicron Permalloy strip

Abstract: We measured ferromagnetic resonance of a single submicron ferromagnetic strip, embedded in an on-chip microwave transmission line device. The method used is based on detection of the oscillating magnetic flux due to the magnetization dynamics, with an inductive pick-up loop. The dependence of the resonance frequency on applied static magnetic field agrees very well with the Kittel formula, demonstrating that the uniform magnetization precession mode is being driven.Recent discoveries of novel phenomena in meso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 15 publications
5
22
0
Order By: Relevance
“…6͑b͔͒ gives ␥ = 176 GHz/ T, and N ʈ 0 M S = 60 mT, N Ќ 0 M S = 930 mT, consistent with earlier reports. 26,43 The fit confirms that the dc voltage appears at the uniform ferromagnetic resonance mode of the Py strip. The measured amplitude of the dc voltage as a function of the square of the applied rf current, at 13 GHz and 139 mT is shown in Fig.…”
Section: A Detection Of Spin Pumpingsupporting
confidence: 62%
See 2 more Smart Citations
“…6͑b͔͒ gives ␥ = 176 GHz/ T, and N ʈ 0 M S = 60 mT, N Ќ 0 M S = 930 mT, consistent with earlier reports. 26,43 The fit confirms that the dc voltage appears at the uniform ferromagnetic resonance mode of the Py strip. The measured amplitude of the dc voltage as a function of the square of the applied rf current, at 13 GHz and 139 mT is shown in Fig.…”
Section: A Detection Of Spin Pumpingsupporting
confidence: 62%
“…We have recently shown that a submicron Py strip can be driven into the uniform precession ferromagnetic resonance mode 21,26 by using a small perpendicular rf magnetic field created with an on-chip coplanar strip waveguide 39 ͑CSW͒ positioned close to Py strip ͑similar geometry as shown in Fig. 3͒.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ferromagnetic wires with magnetization, wave vector k, and biasing magnetic field H aligned along the wire have been explored theoretically 10,11 while elegant and powerful Brillouin light scattering experiments document thermally excited lateral standing wave patterns associated with the various spin wave modes. [12][13][14] Here we use shorted coplanar waveguides 15,16 to excite and detect BVMSWs in spin waveguides and directly measure the spin wave dispersion and attenuation. Further, we document spin wave "tunneling" through gaps in the wires produced by focused ion beam ͑FIB͒ etching.…”
Section: Dispersion and Spin Wave "Tunneling" In Nanostructured Magnementioning
confidence: 99%
“…We have recently shown [12] that a submicron Py strip can be driven into the uniform precession ferromagnetic resonance mode, using a small perpendicular rf magnetic field created with an on-chip coplanar strip waveguide [13] positioned close to the Py strip (similar geometry as shown in Fig. 1).…”
Section: Prl 97 216603 (2006) P H Y S I C a L R E V I E W L E T T E mentioning
confidence: 99%